Docência universitária no contexto do ensino remoto na UFAM: desafios acadêmico-pedagógicos de professores do IEAA - Alves, Josiliana Abreu (Brasil, 2021)
The work presented "University Teaching in the Context of Remote Teaching at UFAM: Academic-Pedagogical Challenges of IEAA Teachers" focused on higher education professors who teach at the Institute of Education, Agriculture and Environment (IEAA) and are in line with in the current and challenging context of Emergency Remote Education (ERE), which we are experiencing, justified by COVID-19. Higher education professors have academic and pedagogical responsibilities in the process of teaching and learning and, therefore, they make a difference in students' lives. So, giving them time and voice was a possibility for a better understanding of the academic-pedagogical challenges experienced in this context. Our work was in search of answers to the problem: what academic-pedagogical challenges did IEAA professors experience in the context of remote teaching at IEAA/UFAM? Given this concern, the objective was to analyze the academic-pedagogical challenges in the context of remote teaching experienced by IEAA teachers. This objective led the study to a qualitative approach research. Data were collected through a narrative interview and, due to the impossibility of the moment, some were carried out in person and others via Google Meet. The data analyzed showed that the most recurrent academic-pedagogical challenges are related to issues such as: the lack of ability to use digital technologies, both on the part of teachers and students; interaction and participation of students in classes; physical and mental fatigue for demanding more time both when planning classes and when giving them; adaptation of their pedagogical practices for motivation in classes, problems with internet and energy, in addition to the lack of a computer or notebook for students to use in class. All these questions were challenging for academic-pedagogical performance.